Faktor – Faktor Yang Mempengaruhi Kinerja Sistem Informasi Akuntansi Perusahaan Ritel Di Kota Tangerang - Siska Ryadi; Jimmy Ardianto (Ultima Accounting : Jurnal Ilmu Akuntansi, 2014)
The purpose of this research is to analyze the factors that can improve the performance of Accounting Information System (AIS) used in the retail companies. There are four factors in this research, the factors consists user participation, top management support, user capabilities, and training and user education. The objects of this research are the retail companies in Tangerang. The data used in this research is the primary data. The samples in this research are determined based on convenience sampling. The results from this research indicate that training and user education had significant influence to the performance of AIS partially, whereas user participation, top management support and user capabilities had not significant influence to the performance of AIS. Keywords : accounting information systems, AIS performance, user participation, top management support , user capabilities, training and user education .